Influence of Teachers ' Mathematical Knowledge for Teaching on Students ' Academic Achievement in Secondary Mathematics in Tanzania - Mwinuka, Ephely Josephat; Tarmo, Albert Paulo (Papers in Education and Development, 2021)
Abstract This survey investigated the influence of teachers ' Mathematics knowledge for teaching on students ' achievements in ordinary level Mathematics in Mbeya region in Tanzania. Teachers ' questionnaires I and II were administered to 27 ordinary level Mathematics teachers. 5224 Form two students from all community schools in Mbeya did the test. Findings indicate that ordinary level Mathematics teachers have low possession of MKT domains. The differences on students ' achievements based on teachers ' possession of Common Content Knowledge (KCS), Knowledge of Content and Students (KCS), Knowledge of Content and Curriculum (KCC) and Mathematics Knowledge for Teaching (MKT) were verified to be statistically significant at 95% CI. We recommend the increase of teachers ' MKT through in-service training focusing mainly on KCS and SCK which are least possessed MKT domains. Keywords: common content knowledge, knowledge of content and students, mathematical knowledge for teaching, ordinary level mathematics,